THE METHODOLOGY OF ISLAMIZATION OF KNOWLEDGE: A CONCEPTUAL STUDY - Hossain, Muhammad Mostofa; Abdullah, Luqman Haji; Hoque, Muhammad Tazammol; Roslee, Muhammad Ikhlas Bin (International Journal of Islamic Business & Management, 2022)
Islamization of knowledge (IOK) merges ethical principles of Islam with the finest contemporary intelligence to reach a new ijma (consensus) pertinent to divine pieces of knowledge, sciences and scientific methods that are compatible with Islamic teachings, ethics and values. Islamizing knowledge and thought are crucial to attaining the objective of Islam in human existence regardless of their religious or geographical identities. It, therefore, is fit to be incorporated in most pure sciences. The process of IOK often in its commencement emphasizes the style and method above its substance to circulate its essence through an appropriate structure. It values the higher objective, Islamic teachings and ethics in its process, which are Islam's foundation in socio-political and epistemological paradigms. There is an actual obscure for any embryonic paradigm to pattern a dynamic methodology, and IOK is not unconventional from that obscure. Although IOK characteristically upholds its strength in terms of its methodological features of direct and indirect divine scriptures, which remarkably minimize the obstacles in its journey, yet, there is a pressing need for the investigation of current methodology and adoption of newly devised methodologies based on the sources of knowledge and whose proposal is to be the aim of the study. A descriptive approach of the qualitative method will be followed to achieve the study's objective. JEL Classification Codes: I20, I21, I23.